Breeding Young Kazakh White-headed Cattle in Different Calving Seasons - Nasambaev, E.; Akhmetalieva, A.; Nugmanova, A.; Doszhanova, A. (Annals of Agri Bio Research, 2022)
his research was carried out in the breeding farms of the West Kazakhstan region (Aisulu farm, Hafiz farm, Dongelek farm and Plemzavod Chapaevsky LLP). The object of the study was to obtain the young cattle of Kazakh white-headed breed from cows in different calving seasons. Using modern methods of economic analysis in the agro-industrial complex and predicted economic efficiency indices, the authors determined the economic efficiency of raising young animals depending on the calving season. The study of growth and development of young stock was carried out monthly by weighing the calves in the morning before feeding and drinking. Based on the weighing results, the authors determined the following parameters of the productivity of young animals: the live weight of heifers and bulls of the Kazakh white-headed breed of different birth seasons; average daily weight gain of young animals; the features of the exterior and constitution of the young cattle were studied by taking basic measurements of the physique and calculating the physique indices based on them. The data obtained indicated that each farm was characterized by specific conditions for calving according to the seasons of the year, which must be taken into account when organizing herd reproduction and scheduling of mating, insemination and calving.Данные исследования проводились в племенных хозяйствах Западно-Казахстанской области (ФХ «Айсулу», ФХ «Хафиз», ФХ «Донгелек» и ТОО «Племзавод Чапаевский»). Объектом исследования явилось получение молодняка казахской белоголовой породы от коров в разные сезоны отела. Используя современные методы экономического анализа в агропромышленном комплексе и прогнозные показатели экономической эффективности, авторы определили экономическую эффективность выращивания молодняка в зависимости от сезона отела. Изучение роста и развития молодняка проводили ежемесячно путем взвешивания телят в утренние часы перед кормлением и поением. По результатам взвешивания определены следующие параметры продуктивности молодняка: живая масса телок и быков казахской белоголовой породы разных сезонов рождения; среднесуточные привесы молодняка; особенности экстерьера и телосложения молодняка изучались путем проведения основных промеров телосложения и расчета по ним индексов телосложения. Полученные данные свидетельствовали о том, что для каждого хозяйства характерны специфические условия отела по сезонам года, что необходимо учитывать при организации воспроизводства стада и составлении графиков случки, осеменения и отела.
Keywords: импакт-фактор 2022; научный журнал; периодическое издание; зарубежное издание; дальнее зарубежье; скопус; казахская белоголовая порода скота; продуктивность молодняка